Application of Play Therapy to Children's Anxiety Levels Due to Hospitalization - Cindrawati Tahir; Andi Arniyanti (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Introduction: Hospitalization requires the child to stay in the hospital and will undergo treatment until he recovers. This process is unpleasant for children because they will feel traumatised, which causes anxiety. Objective: Knowing the application of play therapy to the level of anxiety in children due to hospitalization. Method: The case study research used is a case report. Results: Based on the data found after the application of play therapy in the results to both clients, both experienced a decrease in anxiety levels; anxiety levels decreased significantly where anxiety levels became mild marks with the face already visibly relaxed, began to interact, and anxiety decreased. Conclusion: The application of play therapy to the level of anxiety of children due to hospitalization has a very influential effect on children